A Gingivektomi dengan metode scalpel pada gingiva enlargement gigi 11 dan 21 - Chaerita Maulani; Lia Amalia (Lembaga Penelitian Universitas YARSI, 2025)
Introduction: Aesthetic factors greatly affect a person's self-confidence. One of the periodontal tissue conditions that causes many aesthetic complaints is gingival enlargement. Gingivectomy is a treatment that can be done in cases of gingival enlargement. This case report describes the management of gingivectomy using the scalpel method in the case of gingival enlargement of teeth 11 and 21. Case History: A 47-year-old female patient came with complaints of swollen gums in the upper front between the incisors. The patient wants the gums to be treated. Previously, the gums had been operated on in 2014 in Brunei but the gums returned to swelling 8 months later. The management in this case was gingivectomy with the scalpel method, namely sterilization of the operating area and infiltration anesthesia. Making bleeding points using a pocket marker. The incision is made with blades no. 11, 12, 15. Remove granulation tissue, calculus and soft cementum by scaling and root planning, then control bleeding and irrigation. Perform gingivoplasty and irrigation with 10% Nacl and Povidone Iodine. Manipulation and application of periodontal dressing, then the patient was given medication and postoperative instructions. Discussion: In this case the choice of treatment using a scalpel because epithelial regeneration can take place in a short time when compared to laser and electrosurgery. Conclusion: The use of a scalpel can be an alternative to the management of gingivectomy with a relatively low cost and a better incision, creating the least amount of tissue damage and faster healing.